Please Take Me Home : The Story of the Rescue Cat - Campbell, Clare, 1952 or 1953-; Campbell, Christopher, 1951- (London : Corsair, 2017)
Clare Campbell examines the plight of the nation's rescue cats, taking us from the unsentimental horrors they've faced through history through to the emotional happy endings of today. For a long time, stray cats in Britain were seen as a pest and hunted down as vermin. Having invited this wild, independent creature into our homes, humans did not extend their welcome for long. Millions of cats were abandoned and left to live on the margins of survival. The few who sought to rescue them were derided as 'mad'. A Princess of Wales was even told to stop helping lost cats in order to avoid a royal scandal; the story was kept a high secret of state for years. It would take over a century for strays to become the nation's beloved pet and internet sensation - the rescue cat. Please Take Me Home is packed with stories of the bravery and loyalty of our feline friends, however badly we treated them. Along the way, we learn the touching narratives of the many amazing people who did care for strays and were doubtless loved in return.
Includes bibliographical references
Keywords: Cats -- Great Britain -- History; Cat rescue -- Great Britain -- History; Cats -- Great Britain -- Anecdotes; Human-animal relationships; Animal rescue